2022
DOI: 10.1007/s11845-021-02867-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of home-based high-intensity interval training versus moderate-intensity continuous training in patients with myocardial infarction: a randomized controlled trial

Abstract: Background Supervised high-intensity interval training (HIIT) has been proposed to be more effective than moderateintensity continuous training (MICT) for improving exercise capacity, but there are not sufficient information effects of home-based HIIT and MICT in patients with myocardial infarction (MI). Aims To compare the effects of home-based HIIT and MICT in patients with MI. Methods Twenty-one patients with MI were randomly assigned to one of two home-based exercise modes: HIIT group and MICT group. Home-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The study participants were predominantly (11/25 studies) patients with coronary heart disease. The remaining studies involved patients with HF 24 , 26 , 38 , 43 , tetralogy of Fallot 12 , heart transplantation 27 , 36 , coronary artery bypass grafting 44 , atrial fibrillation 47 , myocardial infarction 34 , stroke 37 , and hypertension 35 , 41 . Most of the studies reported the registration numbers, while eight did not 25 , 26 , 32 , 34 , 42 44 , 46 .…”
Section: Resultsmentioning
confidence: 99%
“…The study participants were predominantly (11/25 studies) patients with coronary heart disease. The remaining studies involved patients with HF 24 , 26 , 38 , 43 , tetralogy of Fallot 12 , heart transplantation 27 , 36 , coronary artery bypass grafting 44 , atrial fibrillation 47 , myocardial infarction 34 , stroke 37 , and hypertension 35 , 41 . Most of the studies reported the registration numbers, while eight did not 25 , 26 , 32 , 34 , 42 44 , 46 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, evidence shows that these programs are effective in varying clinical contexts, including home and intensive care units. [27][28][29] Low-volume, high-intensity interval exercise programs, although shorter in overall length, still improve overall function, strength, aerobic capacity, and physiological biomarkers. Overall training time is less than 15 minutes (not including warmup or cool down), and a starting interval time of 30 seconds has been recommended to provide increased flexibility for progression/regression in response to patient needs.…”
Section: Construction Of High-intensity Interval Training Programs: H...mentioning
confidence: 99%
“…In addition, evidence shows that these programs are effective in varying clinical contexts, including home and intensive care units. 27-29…”
Section: Construction Of High-intensity Interval Training Programs: H...mentioning
confidence: 99%
“…In the acquisition of experience by the team in charge of performing the evaluations, Rodríguez, in 2015 showed that an experienced evaluator has a regular to good reliability (intraclass correlation coe cient [ICC] = 0.70) [9]. On the other hand, Yakut et al, (2022) compared two home training protocols, one was a high-intensity interval training and the other was a moderate-intensity continuous training. In both groups, the MIP, functional capacity, and quality of life increased.…”
Section: Introductionmentioning
confidence: 99%
“…In both groups, the MIP, functional capacity, and quality of life increased. The researchers attributed these changes to the effect of learning the technique and the development of skills to perform the MIP, however, neither the form nor the time to acquire it was analyzed [10].…”
Section: Introductionmentioning
confidence: 99%